Developmental origins of hematopoietic stem cells. - Robin, C; Ottersbach, K; De Bruijn, M; Ma, X; van der Horn, K; Dzierzak, E (2003)
Hematopoietic stem cells (HSCs) are at the foundation of the hematopoietic hierarchy and give rise to all blood lineages in the adult organism. A thorough understanding of the molecular, cellular, and developmental biology of HSCs is of fundamental importance, but is also clinically relevant for the advancement of cell replacement therapies and transplantation protocols in blood-related genetic disease and leukemias. While the major anatomical sites of hematopoiesis change during ontogeny, it was long believed that the developmental origin of the adult mammalian hematopoietic system was the yolk sac. However, current studies have shown that the first adult-type HSCs are autonomously generated in the intrabody portion of the mouse embryo, the aorta-gonads-mesonephros (AGM) region, and sublocalize to the dorsal aorta. HSCs are also found in the other large embryonic vessels, the vitelline and umbilical arteries. The intraluminal hematopoietic clusters along these vessels, together with the role of the Runx1 transcription factor in cluster and HSC formation and the HSC/endothelial/mesenchymal Runxl expression pattern, strongly suggest a vascular endothelial/mesenchymal origin for the first HSCs. Moreover, a transgenic mouse line expressing the GFP marker under the control of the Sca-1 transcriptional regulatory elements (GFP expression marks all HSCs) shows a clear localization of GFP-expressing cells to the endothelial cell layer of the dorsal aorta. Thus, highly enriched GFP-positive AGM HSCs will serve as a basis for the future examination of the cellular and molecular factors involved in the induction and expansion of adult HSCs.